ANALISIS KEPUASAN KERJA TERHADAP KOMPETENSI MELALUI MOTIVASI - Salsabila Dika Ramadhina; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Human resources are one of the most important factors that need to be optimized by the company in order to achieve the company's vision and mission. Job satisfaction is an individual's feelings and assessments about his job, such as job conditions, and the influence of work in meeting his expectations, and needs. PT X offers the best service for its customers. Therefore, PT X highly prioritizes the human resources within the company to provide the best service to the customer. The phenomenon that exists at PT Persada in the last three years before the pandemic, namely in 2017 to 2019, has significantly decreased the number of customer departing. In this study using quantitative research methods conducted at the head office of PT X located in Surabaya. Research using primary data obtained from distributing questionnaires. This research used the entire population as sampling which is 77 respondents. Based on the results of hypothesis testing, researchers found that competence does not significantly affect job satisfaction at PT X. Then, researchers found that competence has a significant effect on motivation in employees of PT X. Later on, testing, researchers found that motivation has a significant positive effect on job satisfaction in employees of PT X. Last, researchers found that Competence has a significant effect on Job Satisfaction through Motivation. In terms of practice, companies should pay more attention to employee job satisfaction to increase employee competence and motivation so that they can help companies achieve their goals.